2018
DOI: 10.1177/1120672118799626
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of addition of nepafenac 0.1% to steroid eye drops in prevention of post-phaco macular edema in high-risk eyes

Abstract: Addition of topical nepafenac eye drops to topical steroid drops significantly reduced the amount of pseudophakic macular edema after cataract surgery in high-risk eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
(62 reference statements)
1
4
0
1
Order By: Relevance
“…They concluded that a three-month use of nepafenac after cataract surgery helps prevent the development of macular edema without any safety concerns. El Gharbway 18 and colleagues studied the effect of nepafenac 0.1% eye drops after cataract surgery in patients (Glaucoma, uveitis, traumatic cataract) who were at high risk of developing post-operative pseudophakic macular edema. The study suggests the use of topical nepafenac eye drops after cataract surgery in high-risk patients as it significantly reduces the incidence of macular edema in pseudophakic patients.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that a three-month use of nepafenac after cataract surgery helps prevent the development of macular edema without any safety concerns. El Gharbway 18 and colleagues studied the effect of nepafenac 0.1% eye drops after cataract surgery in patients (Glaucoma, uveitis, traumatic cataract) who were at high risk of developing post-operative pseudophakic macular edema. The study suggests the use of topical nepafenac eye drops after cataract surgery in high-risk patients as it significantly reduces the incidence of macular edema in pseudophakic patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 56 ] A study reported that topical nepafenac 0.1% combined with topical steroids significantly reduced the incidence of uveitic CME after cataract extraction. [ 57 ] Schallhorn et al . investigated the efficacy of topical difluprednate in uveitic CME and reported improvement or resolution of uveitic CME in most eyes.…”
Section: P Ostoperative C Omplications A...mentioning
confidence: 99%
“…Therapeutic tools available for prophylaxis and treatment of PCME are based on the understanding of these factors and their pathways. The best prophylactic regimen for PCME has not been established, but corticosteroids and topical nonsteroidal anti-inflammatory drugs (NSAIDs), alone or combined have proven to be useful [20][21][22][23] and are extensively used as the first-line drugs 24 . A previous comprehensive study to evaluate PCME prevention after cataract surgery demonstrated that topical therapy with NSAIDs (bromfenac 0.09%) or steroids (dexamethasone 0.1%) alone, was related to a higher incidence of clinically significant PCME 12 weeks postoperatively (incidence of 3.6% and 5.1%, respectively) compared to combined therapy (incidence of 1.5%) 25 .…”
Section: Introductionmentioning
confidence: 99%